2019
DOI: 10.2147/ott.s195205
|View full text |Cite
|
Sign up to set email alerts
|

<p>The reversal of MRP1 expression induced by low-frequency and low-intensity ultrasound and curcumin mediated by VEGF in brain glioma</p>

Abstract: Purpose: To explore the effect of curcumin and low-frequency and low-intensity ultrasound (LFLIU) on C6 and U87 cell, and whether LFLIU could inhibit multidrug resistance protein 1 (MRP1) by increasing the sensitivity of curcumin via vascular epithelial growth factor (VEGF)/PI3K/Akt signaling pathway targeting. Methods: C6 and U87 cells were treated with various doses of curcumin and/or different intensities of LFLIU for 60 s. After 24 hrs, the effects of curcumin and/or LFLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Previously published reports confirmed the ABC transporter expression patterns in U87 and U251 cells in vitro. P-gp and BCRP expression in both U87 and U251 cells were low (Doganlar et al [ 13 ]; Wang et al [ 57 ]; Zhang et al 62 ), while MRP1 was expressed at high levels in both cell lines (Li et al [ 33 ]; Yao and Zhang [ 59 ]). However, no information was available on MRP4 protein expression in U87 and U251 cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published reports confirmed the ABC transporter expression patterns in U87 and U251 cells in vitro. P-gp and BCRP expression in both U87 and U251 cells were low (Doganlar et al [ 13 ]; Wang et al [ 57 ]; Zhang et al 62 ), while MRP1 was expressed at high levels in both cell lines (Li et al [ 33 ]; Yao and Zhang [ 59 ]). However, no information was available on MRP4 protein expression in U87 and U251 cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been observed that, there is a synergistic enhancing effect of VEGF and MDR on the invasion of Hep‐2 cells (Li et al 2009) and VEGF is related to the over‐expression of MRP1 and MDR in glioblastomas (DeLay et al 2012). The VEGF/PI3K/Akt pathway is one of the most important signal pathways in cancers, which is vital to angiogenesis, proliferation, invasion, enhancing cell repair motility and migration ability, and inhibition of apoptosis in cancer cells (Yao and Zhang 2019). A study also proved that, mesenchymal stem cells‐derived exosomes with low‐expressed miR‐153‐3p notably stimulates the activation of Angiopoietin 1 (ANGPT1) and the VEGF/VEGFR2/PI3K/Akt/eNOS pathways, hence prevents the damaged endothelial cells and cardiomyocytes against hypoxia (Ning et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study by our group found that curcumin and ultrasound alone could inhibit the proliferative effect of glioma, and the combination of the two could achieve a better effect (Yao and Zhang 2019). The experiments showed that LFS (low-frequency ultrasound) can effectively open the BBB and ensure normal brain tissue is not damaged, while the opening of the BBB by LFS combined with microbubbles has a higher safety profile, and the cavitation effect of LFS combined with microbubbles greatly enhances the permeability of the cell membrane, and can also make the BBB endothelial cells inter gap widen, so that drugs can more easily enter the BBB.…”
Section: Introductionmentioning
confidence: 85%
“…Vascular endothelial growth factor (VEGF) is a central player in tumor angiogenesis, which is associated with tumor progression and metastasis (Yao and Zhang 2019). Tumor vascularization also plays a significant role in the progression of gliomas and other tumors via activation of the TGF-β1/Smad/PDGF (pro-platelet growth factor) signaling pathway.…”
Section: Introductionmentioning
confidence: 99%